2003
DOI: 10.1016/s1526-9523(02)00421-x
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Women Seek Antenatal Care Late? Perspectives From Rural South Africa

Abstract: Despite the widespread availability of free antenatal care services, most women in rural South Africa attend their first antenatal clinic late in pregnancy and fail to return for any followup care, potentially leading to avoidable perinatal and maternal complications. Using interviews with pregnant women from the rural Hlabisa district of South Africa, we documented perceptions of health and health care during pregnancy and investigated factors shaping the utilization of antenatal care. Our findings indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
134
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(154 citation statements)
references
References 12 publications
19
134
1
Order By: Relevance
“…This finding was consistent with the studies conducted in South Africa [15] Ghana, Kenya and Malawi [16]. This might be due to mothers within this age group have many experience throughout their life time and receive education from health extension works consistently which can help them to resist the elders influence that can prevent them not to follow their FANC.…”
Section: Discussionsupporting
confidence: 90%
“…This finding was consistent with the studies conducted in South Africa [15] Ghana, Kenya and Malawi [16]. This might be due to mothers within this age group have many experience throughout their life time and receive education from health extension works consistently which can help them to resist the elders influence that can prevent them not to follow their FANC.…”
Section: Discussionsupporting
confidence: 90%
“…First attendance at antenatal clinic (first booking) varies but pregnant women in some developing countries, particularly those from poor communities may not start to attend an antenatal clinic until much later in the pregnancy (Lavender, Downe, Finnlayson, & Walsh, 2007;Myer & Harrison, 2003) by which time the effects of low pregnancy weight e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies suggested that most women experienced direct benefit from ANC in various pregnancies complications [40]. Neither urban nor rural women were sure about the benefits of ANC for their health or their unborn child in Zimbabwe [32].…”
Section: Survey Of Literaturementioning
confidence: 99%